Biocomposites based 3D printing, processes and applications: a brief review. (28th February 2022) - Shoeb, Mohd; Kumar, Lokesh; Haleem, Abid
Besides, to fabricate intricate geometric products, additive manufacturing (AM) provides crucial capacities such as flexibility to complement other manufacturing methods and application of different materials at a single manufacturing platform to produce composites multi-material products. 3D printing is one of the major technological platforms of AM and is considered an emerging and effective method towards composites developments due to its various advantages over conventional methods. Biocomposites fabricated using 3D printing technologies show remarkable success to replace traditional non-biodegradable materials. The multi-materials application for assimilated structures has enhanced functionality, reduced weight, and single-stage production. In this work, considering the requirement of a substantial selection of biocomposites constituent and fabrication methods, a literature-based review on biocomposites using 3D technologies have been carried out. For this purpose, the selected research papers from reputed journals have been studied. The biocomposites constituents, 3D printing methods, findings, future scope, and applications are arranged in tabular form with brief descriptions of applications and limitations of 3D printed biocomposites. The theories and methodologies may be used to manufacture 3D printed biocomposites to utilise in the industrial and medical fields.